I Saw it Coming - K'Meyer, T. author. aut Link
XI, 185 p.
Keywords: In this book, workers displaced by plant closings in Louisville, Kentucky tell their stories, emphasizing their agency, demanding respect for their skill, casting judgment on business and government for not showing that respect, and revealing a sense of alienation resulting from violation of their values and trust.